Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijms21020423
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin Extracted from Saffron Shows Antitumor Effects in Models of Human Glioblastoma

Abstract: Over recent years, many authors discussed the effects of different natural compounds on glioblastoma (GBM). Due to its capacity to impair survival and progression of different cancer types, saffron extract (SE), named crocetin (CCT), is particularly noteworthy. In this work, we elucidated the antitumor properties of crocetin in glioma in vivo and in vitro models for the first time. The in vitro results showed that the four tumor cell lines observed in this study (U251, U87, U138, and U373), which were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Radioprotectors targeting oxidative damage and inflammatory reaction have been studied for decades with limited success, because of the limited effect, toxicity or risk of tumorigenesis [ 15 ]. In this context, we have hypothesized the potential of crocetin as a protective agent in relation to its antioxidant, anti-inflammatory and antitumor activities which would facilitate clinical application [ 43 ]. According to [ 32 ], the in vitro culture system selected to test IR and crocetin effects was able to sustain in vitro spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Radioprotectors targeting oxidative damage and inflammatory reaction have been studied for decades with limited success, because of the limited effect, toxicity or risk of tumorigenesis [ 15 ]. In this context, we have hypothesized the potential of crocetin as a protective agent in relation to its antioxidant, anti-inflammatory and antitumor activities which would facilitate clinical application [ 43 ]. According to [ 32 ], the in vitro culture system selected to test IR and crocetin effects was able to sustain in vitro spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of crocetin contains a 20-carbon chain, six double bonds, and two carboxylic acid groups ( Figure 1(a) ). A large number of reports have been demonstrated that crocetin exerts multiple pharmacological properties, such as anti-inflammatory, antioxidant, antifatigue, and anticancer effects [ 8 11 ]. In addition, crocetin was demonstrated to play neuroprotective effects on cerebral ischemia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was possible to observe deep changes in cell morphology and change in mesenchymal and neuronal markers. In addition, crocetin not only had more major effects than radiotherapy alone, but also similar effects to TMZ [ 112 , 113 ]. Another new natural molecule is the PBI-05204 (a supercritical CO 2 extract of Nerium oleander).…”
Section: Novel Anticancer Strategies Targeting Glioblastoma Stem Cellsmentioning
confidence: 99%